Betel leaf extract and its major component hydroxychavicol promote osteogenesis and alleviate glucocorticoid-induced osteoporosis in rats. Issue 14 (8th June 2021) - Mishra, Rutusmita; Das, Neeladrisingha; Varshney, Ritu; Juneja, Kriti; Sircar, Debabrata; Roy, Partha
Abstract : Piper betle leaves possess several ethnomedicinal properties and are immensely used in traditional medicinal practices in regions of Asian and African subcontinents. Abstract : Piper betle leaves possess several ethnomedicinal properties and are immensely used in traditional medicinal practices in regions of Asian and African subcontinents. However, their effects in treating skeletal complications are least known. In this study, we evaluated cellular and molecular effects of betel leaf extract (BLE) and its major phytoconstituent, hydroxychavicol (HCV) in promoting osteogenesis in vitro and alleviating glucocorticoid induced osteoporosis (GIO) in vivo. Both BLE and HCV markedly stimulated osteoblast differentiation of C3H10T1/2 cells with increased expression of RUNX2 and osteopontin through the GSK-3β/β-catenin-signaling pathway. Also, oral administration of BLE and HCV in GIO rats resulted in restoration of bone mass and tissue microarchitecture. Thus, with our findings we conclude that BLE and HCV promote osteogenesis of C3H10T1/2 cells via the GSK-3β/β-catenin pathway and alleviate GIO in rats.